"A Conscience Burning with Impatience": Merton and the Art of Apocalyptic Times. - Pramuk, Christopher (The Merton annual, 2024)
This essay aims to surface Merton's witness to Christian hope in an apocalyptic key, the breakthrough of divine Presence "behind a veil of humility" in times of crisis. Critical to Merton's heightened eschatology and increasingly bold use of biblical imagery is his encounter with the writings of Paul Evdokimov and other Orthodox theologians during the late 1950s. From his prose poems to his drawings and meditations on religious art, Merton's theological imagination reflects "a conscience burning with impatience," articulating hope against the tumultuous signs of the times "in image, in figure, in poem, in vision."